The mediating effect of perceived trust in the adoption of cutting-edge financial technology among digital natives in the post-COVID-19 era - Udit Chawla; Rajesh Mohnot; Harsh Vikram Singh; Arindam Banerjee (Economies, 2023)
The primary aim of this research is to thoroughly examine the determinants that influence customers' intention towards embracing FinTech products and services, thereby enriching our understanding of the adoption and utilization trends within the FinTech industry in the aftermath of the COVID-19 pandemic. This is quantitative research in the context of India covering five major tech-savvy cities-Mumbai, Bengaluru, New Delhi, Pune, and Chennai. Using structural equation modeling (SEM), the mediation effect of Perceived Trust was examined in order to see the relationship between the retrieved constructs and their attributes. Predominantly, the data delve into the utilization of financial technology and the prevailing embrace of this transformative innovation by contemporary Indian society. From the findings, it has emerged that the three factors influencing Customer Intention to Adopt FinTech products are 'Perceived Security', 'Perceived Risks', and 'Perceived Trust'. The significance of Perceived Security in the realm of defending against cyber risks and safeguarding personal information has been discovered to have a profound effect on individuals' inclination to embrace FinTech. Likewise, acknowledging the potential risks and uncertainties that come with FinTech has proven to have a favorable impact on the intention to adopt. Notably, the perception of trust, which encompasses aspects such as the credibility of the company and the user-friendly nature of the technology, has been identified as a significant driver towards adoption.
Keywords: 330; FinTech; Perceived Risk; Perceived Trust; mediating effect; mobile payment; structuralequation modeling (SEM)